Advanced diagnostic endoscopy in the lower gastrointestinal tract: A review of JGES core sessions. Issue 2 (12th December 2017) - Oka, Shiro; Tanaka, Shinji; Sano, Yasushi; Saitoh, Yusuke; Shimoda, Ryo; Tajiri, Hisao
Abstract : At each of the 89th to the 92nd congresses of the Japan Gastroenterological Endoscopy Society, a series of featured discussion sessions concerning advanced diagnostic endoscopy in the lower gastrointestinal tract were presented. In total, 45 lectures were presented in this subject area. It was shown that, in recent years, several convenient and less invasive colonoscopic modalities have been developed. This review article summarizes these core sessions and the efficacy of the techniques discussed.